1969
DOI: 10.1139/f69-170
|View full text |Cite
|
Sign up to set email alerts
|

Greater Dispersal of Wild Compared with Hatchery-Reared Juvenile Atlantic Salmon Released in Streams

Abstract: When wild juvenile (parr) Atlantic salmon (Salmo salar L.) caught by electrofishing, and an equal number of hatchery-reared parr, matched for size with the wild ones, were released at three sites in unfamiliar streams containing resident parr, more hatchery-reared than wild parr could be observed by skin-diving in the areas 1 and 2 weeks later.Observed mortalities of wild parr were not sufficiently higher than those of hatchery parr to explain this result. Nor could a higher proportion of wild parr be found hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…In contrast, the HOR parr from the egg boxes that were placed in the same geographical area as natural redds were (30–50 rkm) dispersed the longest distances (Figure ), which suggests that density‐dependent competition with NOR Chinook Salmon may have influenced the dispersal behavior of the HOR parr. Consistent with prior studies (Symons ; Cresswell ; Weber and Fausch ; Andrews et al. ), we found that NOR fish dispersed greater distances, with an estimated median dispersal distance of NOR parr almost 200% greater than that of HOR fish (Figure ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the HOR parr from the egg boxes that were placed in the same geographical area as natural redds were (30–50 rkm) dispersed the longest distances (Figure ), which suggests that density‐dependent competition with NOR Chinook Salmon may have influenced the dispersal behavior of the HOR parr. Consistent with prior studies (Symons ; Cresswell ; Weber and Fausch ; Andrews et al. ), we found that NOR fish dispersed greater distances, with an estimated median dispersal distance of NOR parr almost 200% greater than that of HOR fish (Figure ).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the HOR parr from the egg boxes that were placed in the same geographical area as natural redds were (30-50 rkm) dispersed the longest distances (Figure 9), which suggests that density-dependent competition with NOR Chinook Salmon may have influenced the dispersal behavior of the HOR parr. Consistent with prior studies (Symons 1969;Cresswell 1981;Weber Figure 8). In addition to the possible role of density-dependent competition, we speculate that this pronounced difference may have been influenced by selection for sedentary habits in multigeneration segregated hatchery broodstocks (Einum and Fleming 2001), environmental differences between the egg boxes and natural redds (e.g., egg incubation temperature, food availability, interactions with resident fish, etc.…”
Section: Objective 3: Performance Of Hor Versus Nor Progenysupporting
confidence: 92%
“…Regardless, the lack of effect on S and φ for wild trout suggests that not only was survival of wild trout unaffected by catchables, but stocking also did not cause any additional emigration when hatchery trout were stocked. Although displacement of wild fish by hatchery fish has been demonstrated in both laboratory and stream settings (see review in Weber and Fausch 2003), including at the reach scale (Symons 1969), our study reaches in general were nowhere near the spatial carrying capacity for wild trout (mean PHS = 20%). Thus, it is not surprising that the addition of hatchery fish caused no additional emigration of wild trout over a level that is considered normal for streamdwelling salmonids.…”
Section: Discussionmentioning
confidence: 89%
“…However, the use of hatchery fish as a surrogate for wild fish is called into question by the many genotypic and phenotypic differences between hatchery and wild fish stocks (Lorenzen et al 2012). Cumulatively, differences in the hatchery environment have the potential to lead to differences in behaviour (Symons 1969;Hill et al 2006;Roberts et al 2011), physiology (Folmar & Dickhoff 1980;Shrimpton et al 1994;Congleton et al 2000), stress response (Pottinger 2006), health and nutritional condition (Wood et al 1957;Ludwig 1982;Powell et al 2010) and ultimately, survival (Kennedy et al 2007) relative to wild conspecifics. In particular, cultured fish are often subjected to disturbance and handling stress in the form of crowding and transfer between tanks, grading and culling, anaesthesia (e.g.…”
Section: Reliance On Hatchery Fishmentioning
confidence: 99%